STROOP INTERFERENCE AND FACILITATION EFFECTS WITH CHINESE CHARACTERS AND PINYIN - Qiu, Yicheng (2023)
The Stroop task has been used to investigate automatic lexical processing and attentional control. Unlike tasks that involve explicit reading (i.e. the lexical decision task), the Stroop task asks for the names of the ink colours, making the word reading task irrelevant. This thesis investigates the Stroop phenomenon by using Chinese characters and pinyin, and how semantic and phonological information provided by Chinese characters and pinyin can be activated in the Stroop task. In Chapter 3, three Stroop experiments are presented that investigated the role of sublexical components (i.e. phonetic radicals) in Chinese characters. When the meaning of the target character is irrelevant to the colour words, its phonetic radical, which is a colour word, can still elicit strong Stroop interference and facilitation effects. This suggests the semantic activation of sublexical components in Chinese characters. Additionally, the phonological cues provided by sublexical components can also be activated in the Stroop task. Chapter 4 Presents a Stroop experiment that explored the decomposed components in Stroop effects. Previous research focussing on multi-stage accounts of Stroop effects confirmed the contribution of response, semantic, and task conflicts. This study provides evidence for the impact of phonological conflicts/facilitation in Stroop effects by using Chinese homophones. A series of Stroop experiments are presented in Chapter 5 that looked at the impact of using Chinese characters written in pinyin, a Romanization transcription of Chinese characters. The results showed that Chinese characters written in pinyin can activate semantic and phonological information of target characters. The mixed presentation of Chinese characters and pinyin in the final experiment suggested that those two scripts can impact each other’s performance in Stroop interference and facilitation effects. The results of this thesis provide new interpretations of the Stroop phenomenon that it can be decomposed into distinct components, including phonological components. In turn, the Stroop task enables the investigation of the automaticity in reading Chinese words, suggesting the role of phonology in the activation of semantics.